Penerapan psikodrama untuk meningkatkan kompetensi emosi pada remaja dengan orang tua bercerai - Ratmilia Cahyani; Siti Suminarti Fasikhah (Universitas Muhammadiyah Malang, 2024)
Adolescents who experience the impact of divorce experience unstable emotional conditions, sadness, disappointment, and low emotional competence. Emotional competence is the condition of an individual who is able to recognize, express, understand, regulate and use the emotions they feel. There are many ways to improve the emotional competence of teenagers with divorced parents, one of which is using the psychodrama method. Psychodrama is a way of expressing what is felt about the pressure or stress that is being experienced or method often called catharsis. The research aims to determine the use of intervention in the form of psychodrama in an effort to increase emotional competence in adolescents with divorced parents. This research uses an experimental approach with a pretest-posttest control group design. The instrument used was the Profile of Emotional Competence (PEC). There were 10 research subjects determined using a purposive sampling method who were then divided into experimental and control groups according to low to medium PEC scores. The results of data analysis using the Wilcoxon test showed that there was a significant difference in the experimental group (p= 0,043) and there was no significant difference in the control group (p= 0,069). Based on these results, it indicates that psychodrama has a significant influence in efforts to increase emotional competence in adolescents with divorced parents.